Febrile seizures and convulsions with mild gastroenteritis: age-dependent acute symptomatic seizures - Cappellari, Alberto M.; Mariani, Stefano; Bruschi, Gaia (Frontiers in Pediatrics, 2023)
Background: Febrile seizures (FS) and benign convulsions in children with mild gastroenteritis (CwG) are acute symptomatic seizures, transiently occurring in infants and young children, probably related to the immaturity of the brain. Our paper aims to review the literature data on patients with FS and CwG. Methods: A review of series of patients with FS and CwG was performed by literature search on PubMed January 1960 to October 2022. Several parameters were considered, including epidemiology, pathophysiology, clinical features, electroencephalographic findings and other diagnostic studies, and treatment. Results: FS and CwG share an age-dependent course, but they show significant differences in the pathophysiology, clinical features, diagnostic studies, and treatment. Conclusion: Acute symptomatic seizures include seizures that are caused by acute structural brain pathologies, such as stroke, as well as seizures that are provoked by a reversible factor, such as hyponatraemia, although the two groups should be not equalled. Furthermore, FS and CwG should be set apart as “age-dependent acute symptomatic seizures”, reinforcing the concept of their self-limited course over a certain period.